Implementasi Kebijakan Survei Kepuasan Masyarakat (Skm) Di Lpse Biro Pengadaan Barang Dan Jasa Provinsi Jawa Timur Pada Tahun 2024 - Kanjeng Ratu, Gusti; Reviandani, Oktarizka (Jurnal Administrasi Publik dan Pemerintahan, 2025)
This study aims to analyze the implementation of the Public Satisfaction Survey (SKM) policy in the Electronic Procurement Service (LPSE) of the Procurement Bureau of East Java Province in 2024. The policy serves as a strategic instrument to measure public participation in public services and evaluate the quality of services provided. This research employs a qualitative method with a descriptive approach, gathering data through interviews, observations, and document analysis related to the implementation of the Public Satisfaction Survey (SKM). The results reveal that the implementation of the SKM policy in the LPSE of the Procurement Bureau of East Java Province in 2024 has been conducted in accordance with established guidelines, supported by the availability of technology that facilitates the survey process. This has resulted in an increase in respondents compared to the previous year, although some members of the public remain reluctant to contribute to the policy's implementation. The study provides strategic recommendations to further improve the implementation of the SKM policy, ensuring the achievement of optimal and sustainable public service delivery.